치과위생사의 전문직업성에 관한 영향요인 연구 - 이지연; Ji Yeoun Lee (Chiwisaeng gwahakoeji, 2011)
The purpose of this study was to examine the professionalism of dental hygienists in dental institutions and the influential factors for their professionalism in an attempt to seek ways of enhancing the professionalism of dental hygienists. The subjects in this study were 172 dental hygienists who worked in dental institutions in Busan and Gimhae. A self-administered survey was conducted to gather data, and an experimental analysis was carried out to analyze the collected data. The major findings of the study were as follows: First, concerning professionalism, self-regulation belief(3.70) ranked highest(3.42), followed by service belief(3.65), autonomy belief(3.31), a sense of vocational calling(3.30) and utilization of the professional organization as a standard(3.12). Second, the professionalism of the dental hygienists was significantly better when their title was higher, when they were older, when they got a larger monthly pay and when they intended to work for a longer time. Third, as for the influential factors for their professionalism, age, marital status, the estimated term of working at the workplace and opinion on reemployment were also identified as the significant variables that were up to the standard level of significance(p=0.05). The findings of the study suggest that in order to boost the professionalism of dental hygienists, it`s required to take institutional measures to give them more responsibility, autonomy and authority, and how to improve personnel administration by providing strong motivation for them to look at their workplaces more favorably and keep on working for a long time should discreetly be considered.